Influence of cell type and virus upon virus-specific immune cytolysis. - Brandt, W E (1975)
Immune cytolysis was measured by release of absorbed radioactive chromium from infected cells that were incubated with antiviral antibody and complement. The presence of virus-specific antigens detected in this manner on the surface of several types of cells infected with Japanese encephalitis (JE) virus did not correlate in each instance with the maturation of infectious virus. JE-infected LLC-MK-2 and Vero cells could not be lysed until long after the first appearance of released virus, and the lysis was minimal in that only a small amount of chromium was released. However, JE-infected BHK-21 and chicken embryo cells could be lysed as soon as new virus was detected in the culture medium, and the lysis reached maximum levels before the time that maximum levels of infectious virus were found in the culture fluids. This phenomenon was restricted to JE virus since BHK-21 cells infected with dengue-2 virus (another group B arbovirus) could not be lysed until well after the appearance of new virus in the culture medium.